Snus and Health: A Review of the Literature on the Impact of Swedish Smokeless Tobacco on the Human Body - Marta Jajczak; Jakub Parys; Agnieszka Mikosińska; Martyna Kaźmierczak; Aleksandra Witek; Maciej Mossakowski; Patrycja Kałuziak; Mateusz Litwin; Stanisław Jesionek (Journal of Education, Health and Sport)
Introduction: Snus is a tobacco-containing product particularly popular in Scandinavian